Earlier occurrence and increased explanatory power of climate for the first incidence of potato late blight caused by Phytophthora infestans in Fennoscandia - Lehsten, Veiko; Wiik, Lars; Hannukkala, Asko; Andreasson, Erik; Chen, Deliang; Ou, Tinghai; Liljeroth, Erland; Lankinen, Åsa; Grenville-Briggs, Laura
2017